Learning in a Pandemi Atmosphere A Study of the Learning Experiences of Island-Based Students at STIKES Hang Tuah Tanjungpinang - Cian Ibnu Sina; Umu Fadhilah (UIN Sunan Gunung Djati Bandung, 2022)
The purpose of this study was to obtain descriptive information about student learning experiences in a pandemic atmosphere due to the impact of Covid-19. The approach uses qualitative methods with in-depth interview techniques to research subjects. In this research the selection of respondents was done deliberately; primary, secondary and tertiary for students from islands who are studying nursing. The results of this study show that online learning during a pandemic or distance is unpleasant and unsatisfactory. In other words, online learning is ineffective due to the atmosphere, besides being supported by unsupportive infrastructure and an unfamiliar distance learning culture.